Diritto penale del lavoro - Smuraglia, Carlo (Milano University Press, 2025)
The republication of the work Diritto penale del lavoro ("Criminal Labor Law"), forty-five years after its original release, is valuable not only for understanding the historical evolution of the subject but also for examining certain key aspects of current legal analysis. Criminal sanctions continue to play a central role—just as they did then—in safeguarding the fundamental rights of individuals against the most serious forms of exploitation and violations of the dignity and physical integrity of workers. However, their purpose is never solely repressive: it is primarily in the realm of prevention—through the most effective tools for preventing the commission of crimes rather than punishing their consequences—that criminal law performs its main function. Hence, Carlo Smuraglia's effort—highly relevant today—to shift the focus toward a broader system of protections, including civil and administrative sanctions, a strong recognition of self-protection rights, an adequate system of oversight, disqualification-type sanctions, and judicial oversight mechanisms.